Butterflies - Saunders-Smith, Gail (Mankato, MN : Capstone, 1998)
Illustrations and simple text describe the life cycle of butterflies.
Includes bibliographical references and index.
1.
P-2.
140
Reading Counts!
Accelerated Reader AR
Keywords: Butterflies -- Life cycles; Butterflies; Insects